An Analysis of Students’ Reading Skill Using Electronic Book to Improve Students’ English Reading Literacy in Elementary School - Made Angga Dwipayana (English Education Department STKIP Agama Hindu Singaraja, 2021)
This study was analyzed student reading skill using electronic book to improve students’ English literacy in elementary school. The subjects of the study were five articles are chosen from how the research to implement electronic book as a teaching tool to improve student reading skill. The data obtained was descriptive qualitative research. This research described the result of using e-book as a teaching tool in elementary school. The data in this study is taken from five articles that examine the use of e-book in elementary school. The result of the study showed that the interesting way to implement reading literacy for teacher in the classroom is using e-book. Electronic book can make students more interested in reading with many features. In addition, the effects of an e-book reading on the following aspects: 1) vocabulary increase, and 2) motivation and interest on reading.